The Application of Isan Folk Wisdom in Producting Creative Short Cultural Films - Chinsorn, Paradon; Suk-erb, Somkhit (Journal of Cultural Approach, 2019)
The objectives of this research were: 1) To study the current state of Isan folk wisdom The objectives of this research were: 1) To study the current state of Isan folk wisdom and 2) To study the application of Isan folk wisdom in short cultural film production. This research was conducted in the northeastern area that uses Isan folk wisdom in the ways of life that are associated to beliefs, traditions, and arts including Mahasarakham, Kalasin, Khon Kaen, Roi–Et and Yasothon province. The research sample is a group of film director, academics, producers, crews and other 82 individuals by using the descriptive analysis for presenting the results. The research found that the history of film creators and film directors are The research found that the history of film creators and film directors are well–known in the film industry for a long time. It is apparent that there is an understanding of the current problems in the production of short films by using the 7 criteria. There are 1) production costs 2) plot/story outline 3) casts 4) scenes and locations 5) crews 6) equipment and 7) duration of studying Isan folk wisdom. In summary, in order to create a short–lived cultural film, one must continue to apply the existing traditional wisdom to maximize the benefit of culture. Importantly, the filmmakers have to discuss and find solutions to common problems so that the film industry that reflects culture, can serve society for a long time.